Psycho-Emotional Factors Associated with Internet Gaming Disorder Among Japanese and Israeli University Students and Other Young Adults - Shai-li Romem Porat; Alexander Reznik; Akihiro Masuyama; Daichi Sugawara; Gal Galya Sternberg; Takahiro Kubo; Richard Isralowitz (Behavioral Sciences, 2025)
Gaming is a popular leisure activity with an increasing number of participants worldwide. It has positive aspects as well as a problematic side—Internet Gaming Disorder (IGD). This behavior attracts concern among mental health and education professionals because of possible negative psycho-emotional factors. This study aimed to assess IGD among Japanese and Israeli university students and other young adults. We explored the association of culture and IGD based on gender, burnout, and loneliness. It was hypothesized that IGD would differentiate based on the respondent country (i.e., Japan or Israel) and gender, with males reporting higher levels. Furthermore, IGD would be associated with higher levels of loneliness and burnout, regardless of country. Qualtrics and Excel platforms were used to collect responses to the Internet Gaming Disorder Scale–Short Form, De Jong Gierveld Loneliness Scale, and Short Burnout Measure (SBM). Data was gathered from a cross-cultural sample of 1318 male and female university students and other young adults in Japan and Israel, between 2022 and 2023. Japanese gamers showed less IGD (p < 0.05); and males evidenced higher levels regardless of their country (p < 0.001). IGD was significantly associated with loneliness (p < 0.001) and burnout (p < 0.001). However, multiple regression analysis showed that IGD is predicted only by burnout and gender (p < 0.001), Adjusted R2 = 0.234. This study provides information for policy, prevention, and intervention purposes targeting burnout particularly among males who are a high-risk group. Additionally, this study contributes to possible joint online program development to reduce IGD among Japanese and Israeli gamers. Further research should examine the association between IGD and loneliness, controlling gender and other factors such as substance use, religiosity, eating behavior, depression, game genre, and motivation to play.